Evaluation of Interprofessional Education on Effective Communication Between Pharmacy and Physician Assistant Students. Issue 2 (5th June 2022) - Volino, Lucio R.; Brust-Sisti, Lindsay A.; Patel, Sarah; Yeh, Dipali; Liu, Mei T.; Cogan-Drew, Thea; Parrott, J. Scott
Abstract : Purpose: The purpose of this study was to assess the effect of Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) on student self-perceived competencies and perceptions of interprofessional (IP) communication and teamwork in a clinical case review activity. TeamSTEPPS is an evidence-based curriculum that is used to enhance and support IP healthcare communication. Methods: A repeated-measures, pretest/posttest study evaluated physician assistant students' and student pharmacists' perceptions of TeamSTEPPS. Students completed Performance Assessment for Communication and Teamwork (PACT) surveys, evaluating teamwork, knowledge, attitudes, and skills perceptions before and after a TeamSTEPPS lecture and associated activity with peer feedback. Results: Overall, 87.4% (n = 429) completed pre- and post-PACT surveys. Apart from the Mutual Support domain ( p = .898), all changes were significantly positive ( p < .004), with the greatest improvements occurring in the Attitudes and Perceived Skills domains. Conclusion: TeamSTEPPS IP education, application, and peer feedback improved students' perceptions of multiple domains, including effective communication. Using TeamSTEPPS tools in IP formats enabled the students to safely practice and collaborate in preparation for clinical practice.